Double Cortex Syndrome (Subcortical Band Heterotopia): A Case Report - MOMEN, Ali Akbar; MOMEN, Mehdi (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Momen AA. Momen M. Double Cortex Syndrome (Subcortical Band Heterotopia); A Case Report. Iran J Child Neurol. 2015;9(2):64-68. Abstract Objective Approximately 5–10% of preschool age children are considered developmentally disabled. Brain Magnetic Resonance Imaging (MRI) plays a key role in the diagnostic evaluation in these children. Many congenital or acquired brain anomalies are revealed with MRIs. Although the majority of these abnormalities are sporadic but patients with subcortical band heterotopia or double cortex syndrome have sex-linked inheritance. We are going to present the first case in Iran from Ahvaz city, which was presented with status epilepticus associated with developmental delay and finally diagnosed as double cortex syndrome, because band heterotopia cases especially for continuous or generalized form is rare. A 4.5-year-old developmentally delayed girl was admitted for generalized tonic clonic seizure attack of 1 hr, upward gaze, locked mouth, and urinary incontinence (status epilepticus) in the child neurology ward. She had a history of recurrent seizures that started as febrile seizures since she was 12 months of age and had frequent admissions for having recurrent seizure attacks. She was the only child of consanguineous parents with negative family history of any neurologic problems. She was a product of uneventful term pregnancy, vaginal delivery with a low Apgar score at birth who was admitted for six days in the neonatal ward for hypotonia and cyanosis. At 4.5 years of age, she had HC: 45cm (<3%) Length: 102 cm (25–75%), and BW: 18kg (75%). She was able to sit, walk with support, speak a few words, and communicate with others. A physical exam was unremarkable. Lab data including CBC, blood biochemical, and urinalysis results were all within normal limits, but the electroencephalography (EEG) revealed generalized poly spike-wave discharges. A brain MRI showed corpus callosal dysplasia, generalized band heterotopia, and polymicrogyria. She was discharged home with oral valproate and regular outpatient follow-ups. In the diagnostic evaluation of developmentally delayed and epileptic children, a brain MRI is strongly recommended for accurate diagnosis of anomalies such as neuronal migration disorders (band heterotopia) and others, because appropriate therapeutic management, prognosis, prevention, and genetic counseling for prenatal diagnosis are dependent on definite diagnosis of the proband case.